PELUANG PENDIRIAN KOPERASI UNTUK KESEJAHTERAAN PETANI KARET DI DESA JENGGALU KABUAPATEN SELUMA - Bella Wita Mutiara (JURNAL BUANA, 2022)
The purpose of this study was (1) to find out the opportunities for establishing a cooperative for rubber farmers (2) to analyze the SWOT opportunity for the establishment of a rubber farmer cooperative in Jenggalu Village, Sukaraja District, Seluma Regency. This type of research is qualitative research. The data analysis technique used is the SWOT analysis. The informants involved in this study were rubber farmers and officials from Jenggalu Village. The results of this study are (1) community perceptions and responses given to the community are positive and have a pretty good chance, this is evidenced by the fact that the community will also participate in cooperative management. Social and economic aspects, it has great potential for the establishment of cooperatives aimed at the welfare of rubber farmers. (2) the SWOT analysis that has been carried out shows that the opportunity to establish a cooperative for the welfare of rubber farmers in the rapid growth strategy. This research is useful as a government extension program to eradicate poverty that occurs in rubber farmers. Therefore, the aim of this cooperative is to be able to make rubber farmers prosperous.